Pengelolaan Habitat dan Satwa Penyu Laut - Agus Priyono (Media Konservasi, 1989)
The economic value of sea turtles, their eggs, meats and shells had caused intensive hunting in almost alI over the world. Current protection in Indonesia on sea turtles is still limited on leatherbackturtle (Dermochelys coriacea), olive ridley (Lepidochelys olivacea) and loggerhead (Caretta caretta), three of the five species existing in Indonesia. Attempts to recover their populations had been carried out in Indonesg, comprising : nesting beaches protection, artiflcial incubation and rearing their juveds in the beaches before releasing them to the sea. The artificial incubation had been successful.